Characteristics of Bird Nestling Trees in the Padang State University, West Air Tawar, West Sumatera - Febrinal Febrinal; Fingki Alvia Chandra; Rijal Satria; Ramadhan Sumarmin (Bioscience, 2020)
The purpose of this research is to describe the characteristic of the tree as birds nesting at State University of Padang , West Air Tawar, West Sumatra. This research conducted on March 2019. Data collection was using survey method. The results showed that found 14 species of tree is using by birds to nesting. The characteristic of tree is preferable by birds to using for nesting are tree and pole growth rate, monopodium and simpodium branching type, with round, oval and fountain canopy type, model leeuwenberg, attims and corner architecture model.